2022
DOI: 10.1007/s11192-022-04418-2
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of COVID-19 pre-prints

Abstract: To examine the reproducibility of COVID-19 research, we create a dataset of pre-prints posted to arXiv, bioRxiv, and medRxiv between 28 January 2020 and 30 June 2021 that are related to COVID-19. We extract the text from these pre-prints and parse them looking for keyword markers signaling the availability of the data and code underpinning the pre-print. For the pre-prints that are in our sample, we are unable to find markers of either open data or open code for 75% of those on arXiv, 67% of those on bioRxiv, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…In this study we verified previous code transparency results [10, 11], finding that less than 20% of randomly selected infectious disease modelling studies provide working links to code. Notably, the top-cited set of studies released code far more frequently (48%); however this is may be a function of the journals in which these articles were published and the mandates which they impose.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study we verified previous code transparency results [10, 11], finding that less than 20% of randomly selected infectious disease modelling studies provide working links to code. Notably, the top-cited set of studies released code far more frequently (48%); however this is may be a function of the journals in which these articles were published and the mandates which they impose.…”
Section: Discussionsupporting
confidence: 86%
“…Recently, Zavalis et al [10] evaluated the transparency of published articles in infectious disease modelling by recording the number of papers that had publicly released accompanying code. They found that few authors (20%) share their code, with Collins et al [11] obtaining similar results for COVID-19 preprints 1 (21-33%). These release rates align with other computational domains such as machine learning (33%) [12] and physics (6%) [13].…”
Section: Introductionmentioning
confidence: 74%
“…More literature searches identified another 44 eligible reports for inclusion, giving a total of 114 eligible meta-research studies examining a combined total of 2 254 031 primary articles for the review. 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 ...…”
Section: Resultsmentioning
confidence: 99%
“…Supplementary results in the supplementary information provides further information on the individual participant data retrieval process, as well as the outcomes of the data integrity checks. In total, 108 reports of 105 meta-research studies assessing a total of 2 121 580 primary articles were included in the quantitative analysis, 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 ...…”
Section: Resultsmentioning
confidence: 99%
“…Many authors (e.g. Gustot 2020; Sumner et al 2020; Collins and Alexander 2022) have emphasized the importance of reproducing COVID‐19 research and have begun to catalog the availability of code and data within the literature. Geographers have produced similar catalogs of geographical analyses of COVID‐19 but have limited their reviews to listing and categorizing the literature by topical focus and methodological approach (Agbehadji et al 2020; Ahasan et al 2020; Franch‐Pardo et al 2020, 2021).…”
Section: Empirical Context and The Selection Of Studies For Reproductionmentioning
confidence: 99%